Novel Broadband Dielectric Resonator Antennas Fed Through Double-Bowtie-Slot Excitation Scheme - Almpanis, G.; Fumeaux, C.; Vahldieck, R. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper discusses the concept and the realization of novel wideband dielectric resonator antennas (DRAs), in which a dielectric cylinder or parallelepiped are fed from a microstrip line through two parallel bowtie-slots. The concept of partial independence of the slot modes from the dielectric resonator mode is exploited in such a way that the resonances of the slot modes and of the DRA are designed to occur at different frequencies. As a result, the bandwidth of the DRA is significantly improved, while stability in the radiation patterns and low cross-polarization are maintained. Finally, a study is performed concerning the influence of the gap between the dielectric resonator and the ground plane upon the overall performance of the DRA. Comparison of the results from a commercial software tool (HFSS®) and from the Finite-Volume Time-Domain (FVTD) method is made.